Epigenetic Features of HIV-Induced T-Cell Exhaustion Persist Despite Early Antiretroviral Therapy - Martin, Genevieve E.; Sen, Debattama R.; Pace, Matthew; Robinson, Nicola; Meyerowitz, Jodi; Adland, Emily; Thornhill, John P.; Jones, Mathew; Ogbe, Ane; Parolini, Lucia; Olejniczak, Natalia; Zacharopoulou, Panagiota; et al. (Frontiers in Immunology, 2021)
T cell dysfunction occurs early following HIV infection, impacting the emergence of non-AIDS morbidities and limiting curative efforts. ART initiated during primary HIV infection (PHI) can reverse this dysfunction, but the extent of recovery is unknown. We studied 66 HIV-infected individuals treated from early PHI with up to three years of ART. Compared with HIV uninfected controls, CD4 and CD8 T cells from early HIV infection were characterised by T cell activation and increased expression of the immune checkpoint receptors (ICRs) PD1, Tim-3 and TIGIT. Three years of ART lead to partial – but not complete – normalisation of ICR expression, the dynamics of which varied for individual ICRs. For HIV-specific cells, epigenetic profiling of tetramer-sorted CD8 T cells revealed that epigenetic features of exhaustion typically seen in chronic HIV infection were already present early in PHI, and that ART initiation during PHI resulted in only a partial shift of the epigenome to one with more favourable memory characteristics. These findings suggest that although ART initiation during PHI results in significant immune reconstitution, there may be only partial resolution of HIV-related phenotypic and epigenetic changes.